ICT-based social science learning management with Nearpod application in primary education - Paais, Reinhard Leonardo; Satyawati, Sophia Tri; Iriani, Ade (Jurnal Inovasi Teknologi Pendidikan, 2025)
The integration of technology into education enhances learning experiences, one of which is through the use of Nearpod. The objectives of this study are to (1) describe ICT-based social science learning management through the use of the Nearpod application in primary education and (2) describe the participation of primary education students in social science learning and their responses to the use of the Nearpod application. This qualitative research involved a social sciences teacher and seventh-grade students at YSKI Christian Middle School Semarang. Data were collected through observations, interviews, and documentation and validated using triangulation techniques. The findings reveal that Nearpod-based learning management includes careful planning with lesson plans and interactive activities, implementation through apperception, interactive videos, and PowerPoint slides, and evaluation using game features like Matching Pairs and Time to Climb. Students responded positively, highlighting Nearpod's ease of use, engaging activities, and real-time feedback, though some faced time constraints. This study contributes to the utilization of Nearpod in ICT-based social studies learning, increasing student engagement, and providing insight into the effectiveness of Learning Management Systems (LMS) in elementary education in Indonesia. Further research is recommended to explore Nearpod's effectiveness across subjects and educational levels to enhance teaching methods and student engagement.